2020
DOI: 10.22146/gamaijb.56583
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Degree of Misfit Between Human Resources Management Practices and the Types of Organizational Culture on Organizational Performance

Abstract: “Fit model” argues that the level of misfit between human resources management (HRM) practices and the type of organizational culture negatively influences organizational performance. However, the lack of emprirical research to support that contention can be problematic. Utilizing the concept of fit, this study aims to examine empirically the effect of the degree of misfit between HRM practices and the types of organizational cultures on organizational performance. Data were collected from a sample comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…Moreover, the fit between HRM practices and organizational culture is essential. Kismono & Ramadista (2020) discussed how the misfit between HRM practices and organizational culture can negatively impact organizational performance (Kismono & Ramadista, 2020;. Chatterjee et al, 2018) revealed that individual perceptions of organizational culture significantly impact the learning transfer environment within organizations (Chatterjee et al, 2018).…”
Section: Contextual Factors That Influence the Relationship Between H...mentioning
confidence: 99%
“…Moreover, the fit between HRM practices and organizational culture is essential. Kismono & Ramadista (2020) discussed how the misfit between HRM practices and organizational culture can negatively impact organizational performance (Kismono & Ramadista, 2020;. Chatterjee et al, 2018) revealed that individual perceptions of organizational culture significantly impact the learning transfer environment within organizations (Chatterjee et al, 2018).…”
Section: Contextual Factors That Influence the Relationship Between H...mentioning
confidence: 99%
“…22 Pradana & Kismono aseguran que es necesario destacar que pueden lograrse diferentes tipos de desempeños organizacionales al efectuar una combinación de estrategias o una estrategia específica, por el contrario, se puede implementar una táctica para lograr varios desempeños organizacionales. 24 Zheng et al relacionaron la cultura de la empresa con el desempeño organizacional a través de prácticas de conocimiento, donde la estructura, la estrategia y la efectividad organizacional se tornan decisivas al analizar las prácticas de gestión. El desempeño debe evaluarse tomando en consideración las características de la organización junto con los factores que la componen.…”
Section: Desempeño Organizacionalunclassified
“…Este hallazgo esta en línea con la literatura consultada y entre los autores destacan Pradana & Kismono quienes aseguran en su estudio que una correcta implementación de las prácticas de gestión de recursos humanos dará como resultado un mayor desempeño organizacional. 24 Chopra por su parte asegura que la comprensión del vínculo casual entre las prácticas de GERH y el desempeño organizacional de las empresas permite a los gerentes o administradores de recursos humanos diseñar programas que conduzcan a mejores resultados operativos. 4…”
Section: Prueba De Hipótesisunclassified